Three stories about the conduct of science: Past, future, and present - Neylon, Cameron (BIOMED CENTRAL LTD, 2011)
In this piece I would like to tell a few stories; three stories to be precise. Firstly I want to explain where I am, where I've come from and what has led me to the views that I hold today. I find myself at an interesting point in my life and career at the same point as the research community is undergoing massive change. The second story is one of what the world might look like at some point in the future. What might we achieve? What might it look like? And what will be possible? Finally I want to ask the question of how we get there from here. What is the unifying idea or movement that actually has the potential to carry us forward in a positive way? At the end of this I'm going to ask you, the reader, to commit to something as part of the process of making that happen. © 2011 Neylon; licensee Chemistry Central Ltd.